Exploring the dual functionality of an ytterbium complex for luminescence thermometry and slow magnetic relaxation. Issue 28 (11th June 2019) - Brunet, Gabriel; Marin, Riccardo; Monk, Melissa-Jane; Resch-Genger, Ute; Gálico, Diogo A.; Sigoli, Fernando A.; Suturina, Elizaveta A.; Hemmer, Eva; Murugesu, Muralee
Abstract : A combined experimental and theoretical approach reveals the intricacies related to an Yb III complex, which functions dually as a SMM and a luminescent thermometer. Abstract : We present a comprehensive investigation of the magnetic and optical properties of an ytterbium complex, which combines two desirable and practical features into a single molecular system. Based upon Yb III ions that promote near-infrared optical activity and a chemical backbone that is ideal for an in-depth understanding of the magnetic behaviour, we have designed a multifunctional opto-magnetic species that operates as a luminescent thermometer and as a single-molecule magnet (SMM). Our magnetic investigations, in conjunction with ab initio calculations, reveal one of the highest energy barriers reported for an Yb III -based complex. Moreover, we correlate this anisotropic barrier with the emission spectrum of the compound, wherein we provide a complete assignment of the energetic profile of the complex. Such studies lay the foundation for the design of exciting multi-faceted materials that are able to retain information at the single-molecule level and possess built-in thermal self-monitoring capabilities.